IMPROVING MOTIVATION AND UNDERSTANDING OF FLOOR EXERCISES THROUGH CONTEXTUAL INSTRUCTIONAL VIDEOS FOR STUDENTS WITH LEARNING DIFFICULTIES - Eliyansyah Eliyansyah; Erwin Setyo Kriswanto; Lantip Diat Prasojo; Eka Sapti Cahya Ningrum; Shely Cathrin (PT Altin Riset Publishing, 2026)
This study aimed to improve learning motivation and understanding of floor-gymnastics material through the implementation of contextual video-based instructional media among seventh-grade slow-learning students at SMP Negeri 1 Sandaran. The study employed a quantitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, comprising planning, action, observation, and reflection stages. The research was conducted in two cycles, with each cycle consisting of two instructional meetings. The participants were three purposively selected slow-learning students. Data were collected through learning motivation observations, floor-gymnastics performance assessments, and documentation. The data were analyzed descriptively by comparing students’ achievement across the pre-intervention stage, Cycle I, and Cycle II. The results demonstrated consistent improvements in both learning motivation and understanding of floor-gymnastics material. The mean learning motivation score increased from 50.00% at the pre-intervention stage to 67.50% in Cycle I and 85.00% in Cycle II. Meanwhile, the mean understanding score increased from 54.00 at baseline to 70.00 in Cycle I and 86.00 in Cycle II. Learning mastery increased from 0% at baseline to 66.67% in Cycle I and reached 100% in Cycle II. These improvements indicate that contextual video-based instructional media can support students in understanding movement sequences through visual, repetitive, concrete, and experience-based learning. Therefore, contextual video-based instruction has potential as an adaptive instructional strategy for improving learning motivation and understanding among slow-learning students in physical education, particularly in floor gymnastics.